ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN FORKLIFT MERK TOYOTA (Studi pada Pengguna Forklift Merk Toyota di Jakarta) - Affandi, Kevin Carollan; Tri Astuti, Sri Rahayu (Diponegoro Journal of Management, 2017)
This research is aimed to analyze the influence of brand image, price perception, product quality, promotion and Customer relationship management to Toyota brand forklift purchase decision. This study used multiple linear regression analysis with SPSS program. The population used is the customer who had bought Forklift products in PT. Traktor Nusantara. While the sample used as many as 100 people with sample selection techniques non-probability sampling using accidental sampling. The results showed that there is a positive and significant relationship between brand image of the purchase decision, There is a positive and significant relationship between price perceptions of purchasing decisions, There is a positive and significant relationship between product quality to purchase decision, There is a positive and significant relationship between Promotion of purchasing decisions, There is a positive and significant relationship between Customer relationship management to purchase decisions